(untitled) (Journal of the College of Basic Education, 2026)
This study addresses the problem of weak listening skills among fourth-year English language learners and explores the effectiveness of podcasts as an educational tool to enhance this skill. The lack of research on using podcasts to improve listening skills in classrooms, particularly among students learning English as a foreign language, indicates a significant gap in this area. The study aims to determine whether using podcasts in English language lessons improves students’ listening skills compared to traditional teaching methods. Students who receive their education through podcasts are believed to outperform their peers who receive traditional education on listening comprehension tests. The study included eighty students divided into two groups: an experimental group using podcasts as a supplementary learning tool, and a control group receiving traditional education. A questionnaire was used to gather students’ feedback on podcast use, and pre- and post-tests were administered to assess their improvement. To enhance engagement and assess comprehension, students were also introduced to audio-visual podcasts. According to the results, the experimental group significantly outperformed the control group in listening comprehension, and the students expressed positive opinions about using podcasts in learning.